2015
DOI: 10.4103/2230-8229.149581
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water quality and public health in Southwestern Saudi Arabia: The need for a national monitoring program

Abstract: Aim of the Study:The aim was to investigate the bacteriological quality of drinking water, and explore the factors involved in the knowledge of the public about the quality of drinking water in Najran region, Saudi Arabia.Study Design:A cross-sectional descriptive study.Materials and Methods:A total of 160 water samples were collected. Total coliforms, fecal coliform, and fecal streptococci were counted using Most Probable Number method. The bacterial genes lacZ and uidA specific to total coliforms and Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
5
1
1
Order By: Relevance
“…In contrast,Parvez et al (2016) identified 44.45% E. aerogenes from drinking water which was higher than this study. In case of S. epidermidis,Santos et al (2023) identified 40.6% (26/64) drinking water samples from 15 public fountains located in four urban parks of São Paulocity (Brazil) Alqahtani et al (2015). found S. epidermidis (5.9%) in drinking water in Najran region, Saudi Arabia which is lower than present study.…”
contrasting
confidence: 72%
“…In contrast,Parvez et al (2016) identified 44.45% E. aerogenes from drinking water which was higher than this study. In case of S. epidermidis,Santos et al (2023) identified 40.6% (26/64) drinking water samples from 15 public fountains located in four urban parks of São Paulocity (Brazil) Alqahtani et al (2015). found S. epidermidis (5.9%) in drinking water in Najran region, Saudi Arabia which is lower than present study.…”
contrasting
confidence: 72%
“…A high indicator of fecal coliforms was a universal factor in the water samplings. Such contamination is commonly found in rural areas due to cattle breeding 22 , open defecation 23 , personal hygiene habits carried out close to or inside the water source and improper manipulation, transportation and storage of water from source to households 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…La alta carga de bacterias fecales fue un factor universal en las muestras de agua. Contaminación que es más probable encontrar en zonas rurales debido a actividades pecuarias 22 , defecación al aire libre 23 , aseo personal cercano o dentro de la fuente y manipulación, transporte y almacenamiento inadecuado del agua desde la fuente hasta los hogares 24 , 25 .…”
Section: Discussionunclassified
“…KSA groundwater is drinkable. However, several areas have bacterial contamination due to defective pipelines or obsolete, poorly maintained storage facilities (Alqahtani, et al 2015).…”
Section: Introductionmentioning
confidence: 99%